On a Class of Irreducible Polynomials Over Fp - Kyuregyan, Melsik K.; Harutyunyan, Edita Yu.; Evoyan, Mikayel G. (Mathematical Problems of Computer Science, 2021)
The paper presents some results regarding constructive theory of synthesis of irreducible polynomials of degree pt over Fp from the given primitive elements in Fp, where p is an odd prime and t is an integer whose prime factors all divide p-1.